Загальна модель і методи ієрархічного планування функціонування складних організаційно-виробничих систем із обмеженими ресурсами - Pavlov, A. A.; Misura, E. B.; Melnikov, O. V.; Ruchani, S. A. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
Based on construction features and realization research of the automated hierarchical planning model for small-scale manufacture in market conditions, the general mathematical model for hierarchical planning is formalized that takes into account network representation of technological processes and limited resources and is directed to profit maximisation in complex organisational and production systems. Real classes of objects are determined, for which the offered model is adequate. It is shown how the mathematicware of three-level planning model for small-scale manufacture may be used for these objects functioning planning.